1992
DOI: 10.1111/j.1423-0410.1992.tb01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Miltenberger Subsystem of the MNSs Blood Group System: Review and Outlook

Abstract: The Miltenberger (Mi) classes represent a group of phenotypes for red cells that carry low frequency antigens associated with the MNSs blood group system. The antigens of this system are known to be located on two sialoglycoproteins denoted as glycophorin A (GP A) and GP B. The structural alterations of seven (classes I, II, III, V, VI, VII, VIII) Mi variants and a related variant (J.L.) have been elucidated. Based on these data and yet incomplete studies of the Mi antigens, the approximate structural alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…From the outset, the serological testing was complicated because few of the reactive sera were monospecific. By 1992, the Miltenberger subsystem had expanded to 11 classes [4]. Although a sequence of amino acids representing the elusive Mi a determinant had been proposed [4], there was increasing doubt as to the existence of the Mi a antigen as, at that time, a separate anti-Mi a had not been found nor could it be isolated from the serum of Mrs. Miltenberger.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the outset, the serological testing was complicated because few of the reactive sera were monospecific. By 1992, the Miltenberger subsystem had expanded to 11 classes [4]. Although a sequence of amino acids representing the elusive Mi a determinant had been proposed [4], there was increasing doubt as to the existence of the Mi a antigen as, at that time, a separate anti-Mi a had not been found nor could it be isolated from the serum of Mrs. Miltenberger.…”
Section: Introductionmentioning
confidence: 99%
“…By 1992, the Miltenberger subsystem had expanded to 11 classes [4]. Although a sequence of amino acids representing the elusive Mi a determinant had been proposed [4], there was increasing doubt as to the existence of the Mi a antigen as, at that time, a separate anti-Mi a had not been found nor could it be isolated from the serum of Mrs. Miltenberger. Almost a decade later, believers in the existence of the Mi a antigen were vindicated by the production of monoclonal anti-Mi a [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…GP.Hop (Mi.IV) was first identified by Cleghorn by using anti‐Mur and anti‐Hil, which distinguished the RBCs of the first propositus (MH) from other examples of RBCs in the Miltenberger subsystem that were reactive with the Milten‐berger serum 12 . GP.Hop is serologically similar to GP.Bun, in that it carries Mur, Hop, MINY, and MUT antigens 13 . However, GP.Hop RBCs are Hil–, TSEN+.…”
mentioning
confidence: 99%
“…Despite being Mur + , Mi.IX cells are MUT − . Mi.XI was added [300] for the phenotypes of two propositi on the basis of the reactions of their red cells with anti -TSEN and -MINY, antibodies that reacted with red cells of some other Miltenberger classes [301,302] . Mi.XI was added [300] for the phenotypes of two propositi on the basis of the reactions of their red cells with anti -TSEN and -MINY, antibodies that reacted with red cells of some other Miltenberger classes [301,302] .…”
Section: He ( Mns6)mentioning
confidence: 99%
“…Production of two murine monoclonal anti -Mi a , however, demonstrated that anti -Mi a could exist as a separate entity [343,344] . Dahr [300] speculated that anti -Mi a might detect the amino acid sequence QTND(M or K)HKRDTY. This sequence represents the junction of the 3 ′ end of GYPA exon 2 and the GYPB -pseudoexon, present in GP(B -A -B).…”
Section: A ( Mns7)mentioning
confidence: 99%